The Absence of the DNA-Dependent Protein Kinase Catalytic Subunit in Mice Results in Anaphase Bridges and in Increased Telomeric Fusions with Normal Telomere Length and G-Strand Overhang - Goytisolo, Fermín A. (American Society for Microbiology, 2001)
The major pathway in mammalian cells for repairing DNA double-strand breaks (DSB) is via nonhomologous end joining. Five components function in this pathway, of which three (Ku70, Ku80, and the DNA-dependent protein kinase catalytic subunit [DNA-PKcs]) constitute a complex termed DNA-dependent protein kinase (DNA-PK). Mammalian Ku proteins bind to DSB and recruit DNA-PKcs to the break. Interestingly, besides their role in DSB repair, Ku proteins bind to chromosome ends, or telomeres, protecting them from end-to-end fusions. Here we show that DNA-PKcs(−/−) cells display an increased frequency of spontaneous telomeric fusions and anaphase bridges. However, DNA-PKcs deficiency does not result in significant changes in telomere length or in deregulation of the G-strand overhang at the telomeres. Although less severe, this phenotype is reminiscent of the one recently described for Ku86-defective cells. Here we show that, besides DNA repair, a role for DNA-PKcs is to protect telomeres, which in turn are essential for chromosomal stability.